Exploring the Promising Role of Guggulipid in Rheumatoid Arthritis Management: An In-depth Analysis - Sahu, Amit; Rathee, Sunny; Jain, Sanjay K.; Patil, Umesh Kumar (Current Rheumatology Reviews, 2024)
Background: Guggulipid, an oleo-gum resin extracted from the bark of Commiphora wightii of the Burseraceae family, holds a significant place in Ayurvedic medicine due to its historical use in treating various disorders, including inflammation, gout, rheumatism, obesity, and lipid metabolism imbalances. Objective: This comprehensive review aims to elucidate the molecular targets of guggulipids and explore their cellular responses. Furthermore, it summarizes the findings from in-vitro, in-vivo, and clinical investigations related to arthritis and various inflammatory conditions. Methods: A comprehensive survey encompassing in-vitro, in-vivo, and clinical studies has been conducted to explore the therapeutic capacity of guggulipid in the management of rheumatoid arthritis. Various molecular pathways, such as cyclooxygenase-2 (COX-2), vascular endothelial growth factor (VEGF), PI3-kinase/AKT, JAK/STAT, nitric oxide synthase (iNOS), and NFΚB signaling pathways, have been targeted to assess the antiarthritic and anti-inflammatory effects of this compound. Results: The research findings reveal that guggulipid demonstrates notable antiarthritic and anti-inflammatory effects by targeting key molecular pathways involved in inflammatory responses. These pathways include COX-2, VEGF, PI3-kinase/AKT, JAK/STAT, iNOS, and NFΚB signaling pathways. in-vitro, in-vivo, and clinical studies collectively support the therapeutic potential of guggulipid in managing rheumatoid arthritis and related inflammatory conditions. Conclusion: This review provides a deeper understanding of the therapeutic mechanisms and potential of guggulipid in the management of rheumatoid arthritis. The collective evidence strongly supports the promising role of guggulipid as a therapeutic agent, encouraging further research and development in guggulipid-based treatments for these conditions.
Keywords: rheumatoid arthritis